Orthodontic diagnosis based on Schwarz analysis among the population of Republika Srpska - Arbutina Adriana; Arapović-Savić Marijana; Umićević-Davidović Mirjana; Kuzmanović-Radman Irena (Serbian Medical Society - Dental Section, Belgrade, 2015)
Introduction In order to establish an accurate diagnosis and proper therapy planning in orthodontics, it is necessary to perform the analysis of transverse and sagittal dental arch development in relation to the facial type of the patient. The aim of this study was to determine sagittal and transverse parameters of dental arches in the population of Republika Srpska (Bosnia and Herzegovina) based on Schwarz analysis. Material and Methods Facial type was determined in 300 patients of both genders, aged 18 to 25, with class I occlusion. After taking impressions of the upper and lower jaw, cast study models were poured and used to determine basic sagittal and transverse parameters of dental arches. The obtained values were compared with the values defined by Schwarz in order to determine the existence of certain variations. Results Out of 300 subjects, 50.33% were dolichofacial, 30.76% were mesofacial and 19.00% were brachyfacial. The average values of anterior width, posterior width and height of dental arch in patients with all three types of face showed lower range of values compared to the values defined by Schwarz, who determined his values by examining the same parameters in the population of Vienna. These parameters did not show linear proportional increase with the increase of the sum of upper incisors, what is the case with the values defined by Schwarz. Conclusion The results of this study showed significant differences compared to Schwarz's values. Modification of the size and shape of dental arch leads to changes in the appearance of patient's face. Therefore, an individual approach during orthodontic diagnosis and treatment planning must be present despite the great importance of biometric standards.